(untitled) (Research, Society and Development, 2024)
Childhood obesity, a growing public health problem, has multiple associated factors, such as poor eating habits and sedentary lifestyle. This integrative review aimed to analyze the effectiveness of physical activity in the prevention and control of obesity in schoolchildren, based on studies published between 2018 and 2023. Regular physical activity emerges as a fundamental strategy to combat childhood obesity, promoting weight loss, improving body composition, and reducing the risk of chronic diseases. The school plays a crucial role in this process, offering an environment conducive to physical activity and health education. However, the research reveals that there are still gaps in the implementation of effective physical activity programs in schools. The review highlights the importance of the joint action of schools, families, and health professionals to promote healthy lifestyles from childhood. The promotion of physical activity in schools should be integrated into the school curriculum and involve all teachers, not limited to physical education classes. Additionally, it is essential that families provide support and encourage physical activity at home. In conclusion, physical activity is a powerful tool for preventing and controlling childhood obesity. The implementation of physical activity programs in schools, combined with other interventions, such as the promotion of healthy eating habits, is essential to ensure that children have a healthier and more active life.